Imidazole grafted nano-silica modified perfluorosulfonic acid proton exchange membrane, its preparation method and application

CN118299627BActive Publication Date: 2026-10-27THINKRE MEMBRANE MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410385207.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-01
Publication Date
2026-10-27
Estimated Expiration
2044-04-01

AI Technical Summary

Technical Problem

目前最为常用的质子交换膜为杜邦公司生产的Nafion系列膜,但其存在阻隔性,化学稳定性、质子电导率和成本等综合性能不能满足技术发展的要求,还有待进一步提升

Benefits of technology

[0013]本发明的有益效果如下:采用特定的方法制备咪唑接枝的纳米二氧化硅,减少亲水性气相二氧化硅表面的羟基对全氟磺酸氟树脂中磺酸基的弱化作用,并且咪唑基的引入还可以增强Donnan排斥效应,有效降低钒渗透率。研究发现本发明制备咪唑接枝纳米二氧化硅不仅可以改善全氟磺酸质子交换膜的阻钒性和机械性能,而且可以保持全氟磺酸质子交换膜的高质子电导率,尤其是经过耐久性测试,其质子电导率依然具备良好的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004770452250000061
    Figure BDA0004770452250000061
  • Figure BDA0004770452250000071
    Figure BDA0004770452250000071
Patent Text Reader

Abstract

The application discloses an imidazole grafted nano-silica modified perfluorosulfonic acid proton exchange membrane and a preparation method and application thereof. The perfluorosulfonic acid proton exchange membrane is prepared by a casting film method from perfluorosulfonic acid resin composite modified material; the perfluorosulfonic acid resin composite modified material comprises perfluorosulfonic acid resin and imidazole grafted nano-silica. The preparation method comprises the following steps: (1) 100 parts of perfluorosulfonic acid resin is dissolved in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; (2) the raw materials of the resin solution containing 100 parts of perfluorosulfonic acid resin and 5-10 parts of imidazole grafted nano-silica are mixed uniformly in a blender in proportion, and a film forming solution is obtained after bubble removal; (3) the film forming solution is cast into a solution to obtain the imidazole grafted nano-silica modified perfluorosulfonic acid proton exchange film. The application can not only improve the vanadium resistance and mechanical properties of the perfluorosulfonic acid proton exchange membrane, but also maintain the high proton conductivity of the perfluorosulfonic acid proton exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of proton exchange membrane technology, specifically to an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane, its preparation method, and its application. Background Technology

[0002] Proton exchange membranes (PEMs) are core components in fuel cells, vanadium batteries, and water electrolysis for hydrogen production. An ideal PEM must possess characteristics such as high proton conductivity, resistance to gas permeation, high mechanical strength, good chemical stability, and low cost. Currently, the most commonly used PEMs are the Nafion series membranes manufactured by DuPont. However, their overall performance, including barrier properties, chemical stability, proton conductivity, and cost, does not meet the requirements of technological development and requires further improvement. Summary of the Invention

[0003] In view of the problems existing in the background art, the purpose of the present invention is to provide an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane and its preparation method. The method involves preparing alkenyl-containing nano-silica and treating it with an alkenyl-containing imidazole compound by electron irradiation to obtain imidazole-grafted nano-silica. This imidazole-grafted nano-silica can not only improve the vanadium barrier properties and mechanical properties of the perfluorosulfonic acid proton exchange membrane, but also maintain the high proton conductivity of the perfluorosulfonic acid proton exchange membrane. In particular, after durability testing, its proton conductivity still has good stability.

[0004] To achieve the above objectives, the present invention provides an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane, which is prepared by a perfluorosulfonic acid resin composite modifier by a casting method; the perfluorosulfonic acid resin composite modifier comprises perfluorosulfonic acid resin and imidazole-grafted nano-silica.

[0005] Optionally, the mass ratio of the perfluorosulfonic acid resin to the imidazole-grafted nano-silica is 100:(5-10).

[0006] Optionally, the perfluorosulfonic acid resin is an H-type resin with sulfonic acid groups.

[0007] Optionally, the imidazole-grafted nano-silica is prepared by irradiation grafting reaction of an imidazole compound with an alkenyl group and hydrophilic nano-silica with an alkenyl group.

[0008] Optionally, the preparation method of the imidazole-grafted nano silica includes the following steps: (1) Weigh 100 parts of nano-sized hydrophilic fumed silica and 12-18 parts of vinyltrimethoxysilane in ethanol solution according to the mass ratio, keep the temperature at 85-90℃ in a grinder and grind for 3-4 hours, take the material and put it into a vacuum drying oven and dry it under vacuum at 105-110℃ for 2-3 hours to obtain hydrophilic nano silica with alkenyl groups; the vinyltrimethoxysilane in ethanol solution is composed of 25wt% vinyltrimethoxysilane and 75wt% ethanol; (2) Mix 100 parts of hydrophilic nano silica with alkenyl groups and 10-15 parts of imidazole compounds with alkenyl groups according to the mass ratio, and irradiate them at a temperature of 105-110℃ with an irradiation dose of 3-3.5 Mrad to obtain imidazole-grafted nano silica.

[0009] Optionally, the alkenyl-containing imidazole compound is one or a combination of 2-vinylimidazole and 2-vinylbenzimidazole.

[0010] The present invention also provides a method for preparing the imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane as described above, comprising the following steps: (1) dissolving 100 parts of perfluorosulfonic acid resin in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; (2) mixing the resin solution containing 100 parts of perfluorosulfonic acid resin and 5-10 parts of imidazole-grafted nano-silica raw material in a mixer in proportion, and obtaining a film-forming liquid after degassing; (3) obtaining the imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane by solution casting.

[0011] Optionally, the specific steps of the casting film formation method are as follows: the film-forming liquid is added to the storage tank of the casting machine, the storage tank is kept at 105-110℃, and the film is cast on the transmission steel belt at 120-140℃ through the casting blade, with a film thickness of 0.05mm; the film is removed from the steel belt, and after fixing each side of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane; the heating and shaping temperature is 160-170℃ and the time is 0.5-1h.

[0012] The present invention also provides an application of the imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane as described above, which can be applied to fuel cells, vanadium batteries and chlor-alkali electrolysis.

[0013] The beneficial effects of this invention are as follows: The imidazole-grafted nano-silica prepared by a specific method reduces the weakening effect of hydroxyl groups on the sulfonic acid groups in perfluorosulfonic acid fluororesin by the surface of hydrophilic fumed silica. Furthermore, the introduction of imidazole groups enhances the Donnan repulsion effect, effectively reducing vanadium permeability. Studies have found that the imidazole-grafted nano-silica prepared by this invention not only improves the vanadium barrier properties and mechanical properties of perfluorosulfonic acid proton exchange membranes but also maintains the high proton conductivity of the perfluorosulfonic acid proton exchange membrane. In particular, after durability testing, its proton conductivity still exhibits good stability. Detailed Implementation

[0014] To make the above-mentioned objects, features and advantages of the invention more apparent and understandable, the specific embodiments of the invention are described in detail below.

[0015] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0016] The imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane according to the present invention is prepared by a perfluorosulfonic acid resin composite modifier by a casting method; the perfluorosulfonic acid resin composite modifier comprises perfluorosulfonic acid resin and imidazole-grafted nano-silica.

[0017] In one embodiment, the mass ratio of the perfluorosulfonic acid resin to the imidazole-grafted nano-silica is 100:(5-10).

[0018] In one embodiment, the perfluorosulfonic acid resin is an H-type resin having sulfonic acid groups.

[0019] In one embodiment, the imidazole-grafted nano-silica is prepared by irradiation grafting reaction of an imidazole compound with an alkenyl group and hydrophilic nano-silica with an alkenyl group.

[0020] In one embodiment, the method for preparing the imidazole-grafted nano-silica includes the following steps:

[0021] (1) Weigh 100 parts of nano-sized hydrophilic fumed silica and 12-18 parts of vinyltrimethoxysilane in ethanol solution according to mass fraction. Grind in a grinder at 85-90℃ for 3-4 hours. Take the material and put it into a vacuum drying oven and dry it at 105-110℃ for 2-3 hours to obtain hydrophilic nano-silica with alkenyl groups. The ethanol solution of vinyltrimethoxysilane consists of 25wt% vinyltrimethoxysilane and 75wt% ethanol. (2) Mix 100 parts of hydrophilic nano-silica with alkenyl groups and 10-15 parts of imidazole compounds with alkenyl groups according to mass fraction. Irradiate the mixture at 105-110℃ with an electron irradiation dose of 3-3.5 Mrad to obtain imidazole grafted nano-silica.

[0022] In one embodiment, the alkenyl-containing imidazole compound is one or a combination of 2-vinylimidazole and 2-vinylbenzimidazole.

[0023] The preparation method of the imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane according to the present invention may include the following steps: (1) dissolving 100 parts of perfluorosulfonic acid resin in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; (2) mixing the resin solution containing 100 parts of perfluorosulfonic acid resin and 5-10 parts of imidazole-grafted nano-silica raw material evenly in a mixer, and obtaining a film-forming liquid after degassing; (3) obtaining the imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane by solution casting of the film-forming liquid.

[0024] In one embodiment, the specific steps of the casting film formation method are as follows: the film-forming liquid is added to the storage tank of the casting machine, the storage tank is kept at 105-110°C, and the film is cast on a transmission steel belt at 120-140°C through the casting blade, with a film thickness of 0.05mm; the film is removed from the steel belt, and after fixing each side of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane; the heating and shaping temperature is 160-170°C, and the time is 0.5-1h.

[0025] The imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane of the present invention can be applied to fuel cells, vanadium batteries and chlor-alkali electrolysis.

[0026] The features and performance of the present invention will be further described in detail below with reference to the embodiments. Unless otherwise specified, the raw materials involved in the embodiments and comparative examples can be obtained commercially.

[0027] Example 1

[0028] (1) Weigh 100 parts of nano-sized hydrophilic fumed silica and 12 parts of vinyltrimethoxysilane in ethanol solution according to mass fraction, grind in a grinder at 85°C for 3 hours, take the material and put it into a vacuum drying oven and dry it at 105°C for 2 hours to obtain hydrophilic nano-silica with alkenyl groups; the vinyltrimethoxysilane ethanol solution is composed of 25wt% vinyltrimethoxysilane and 75wt% ethanol; (2) Mix 100 parts of hydrophilic nano-silica with alkenyl groups and 10 parts of 2-vinylimidazole according to mass fraction, and irradiate it at 105°C with an irradiation dose of 3Mrad to obtain imidazole grafted nano-silica.

[0029] (2) 100 parts of perfluorosulfonic acid resin were dissolved in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%.

[0030] (3) Mix the resin solution containing 100 parts of perfluorosulfonic acid resin and 5 parts of imidazole-grafted nano silica in a mixer in proportion, and obtain the film-forming liquid after degassing.

[0031] (4) The film-forming liquid is added to the storage tank of the casting machine. The storage tank is kept at 105°C. The film is cast on a transmission steel belt at 120°C through the casting blade. The film thickness is 0.05 mm. The film is removed from the steel belt and fixed at each side. It is then placed in an oven for heating and shaping. After cooling to room temperature, an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane is obtained. The heating and shaping temperature is 160°C and the time is 0.5 h.

[0032] Example 2

[0033] (1) Weigh 100 parts of nano-sized hydrophilic fumed silica and 18 parts of vinyltrimethoxysilane in ethanol solution according to mass fraction. Grind in a grinder at 90°C for 4 hours. Take the material and put it into a vacuum drying oven and dry it at 110°C for 3 hours to obtain hydrophilic nano-silica with alkenyl groups. The vinyltrimethoxysilane in ethanol solution is composed of 25 wt% vinyltrimethoxysilane and 75 wt% ethanol. (2) Mix 100 parts of hydrophilic nano-silica with alkenyl groups and 15 parts of 2-vinylimidazole according to mass fraction. Irradiate the mixture at 110°C with an electron dose of 3.5 Mrad to obtain imidazole-grafted nano-silica.

[0034] (2) 100 parts of perfluorosulfonic acid resin were dissolved in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%.

[0035] (3) Mix the resin solution containing 100 parts of perfluorosulfonic acid resin and 10 parts of imidazole-grafted nano silica raw material in a mixer in proportion, and obtain the film-forming liquid after degassing.

[0036] (4) The film-forming liquid is added to the storage tank of the casting machine, the storage tank is kept at 110°C, and the film is cast on the transmission steel belt at 140°C through the casting blade. The film thickness is 0.05 mm. The film is removed from the steel belt, and after fixing each side of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane. The heating and shaping temperature is 170°C and the time is 1 hour.

[0037] Example 3

[0038] (1) Weigh 100 parts of nano-sized hydrophilic fumed silica and 15 parts of vinyltrimethoxysilane in ethanol solution according to mass fraction. Grind in a grinder at 88°C for 3.5 hours. Take the material and put it into a vacuum drying oven and dry it at 108°C for 2-3 hours to obtain hydrophilic nano-silica with alkenyl groups. The vinyltrimethoxysilane in ethanol solution is composed of 25 wt% vinyltrimethoxysilane and 75 wt% ethanol. (2) Mix 100 parts of hydrophilic nano-silica with alkenyl groups and 12 parts of 2-vinylbenzimidazole according to mass fraction. Irradiate the mixture at 108°C with an electron dose of 3.3 Mrad to obtain imidazole-grafted nano-silica.

[0039] (2) 100 parts of perfluorosulfonic acid resin were dissolved in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%.

[0040] (3) Mix the resin solution containing 100 parts of perfluorosulfonic acid resin and 8 parts of imidazole-grafted nano silica in a mixer in proportion, and obtain the film-forming liquid after degassing.

[0041] (4) The film-forming liquid is added to the storage tank of the casting machine. The storage tank is kept at 108°C. The film is cast on a transmission steel belt at 130°C through the casting blade. The film thickness is 0.05 mm. The film is removed from the steel belt and fixed at each side. It is then placed in an oven for heating and shaping. After cooling to room temperature, an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane is obtained. The heating and shaping temperature is 165°C and the time is 0.8 h.

[0042] Comparative Example 1

[0043] Except for the absence of imidazole-grafted nano-silica, the process was the same as in Example 3.

[0044] Comparative Example 2

[0045] Except for replacing imidazole-grafted nano-silica with nano-sized hydrophilic fumed silica, everything else is the same as in Example 3.

[0046] Comparative Example 3

[0047] Except for the direct addition of 2-vinylbenzimidazole without grafting it onto nano-silica, everything else was the same as in Example 3.

[0048] Performance testing

[0049] The membrane thickness, mechanical strength, proton conductivity, and vanadium permeability were tested according to relevant national standards. Specific data are shown in the table below.

[0050]

[0051]

[0052] As can be seen from the examples and comparative data, the present invention utilizes imidazole compounds to graft and modify hydrophilic nano-silica, which can not only improve the vanadium barrier properties and mechanical properties of perfluorosulfonic acid proton exchange membranes, but also maintain the high proton conductivity of perfluorosulfonic acid proton exchange membranes. In particular, after durability testing, its proton conductivity still exhibits good stability.

[0053] The above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A vanadium battery, comprising an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane, characterized in that, It is prepared by casting film formation method from perfluorosulfonic acid resin composite modified material; the perfluorosulfonic acid resin composite modified material contains perfluorosulfonic acid resin and imidazole grafted nano silica; the preparation method of imidazole grafted nano silica includes the following steps: (1) Weigh 100 parts of nano-sized hydrophilic fumed silica and 12-18 parts of vinyltrimethoxysilane ethanol solution according to the mass fraction, keep the temperature at 85-90℃ in the grinding mill and grind for 3-4 hours, take the material and put it into the vacuum drying oven. (1) The alkenyl-containing hydrophilic nano-silica is obtained by vacuum drying at 105-110℃ for 2-3 hours; the ethanol solution of the vinyltrimethoxysilane is composed of 25wt% vinyltrimethoxysilane and 75wt% ethanol; (2) 100 parts of alkenyl-containing hydrophilic nano-silica and 10-15 parts of alkenyl-containing imidazole compounds are mixed evenly according to mass parts, and irradiated with electron at 105-110℃ with an irradiation dose of 3-3.5 Mrad to obtain imidazole-grafted nano-silica.

2. The vanadium battery as described in claim 1, characterized in that, The mass ratio of the perfluorosulfonic acid resin to the imidazole-grafted nano silica is 100:(5-10).

3. The vanadium battery as described in claim 1, characterized in that, The perfluorosulfonic acid resin is an H-type resin with sulfonic acid groups.

4. The vanadium battery according to claim 1, wherein the alkenyl-containing imidazole compound is one or a combination of 2-vinylimidazole and 2-vinylbenzimidazole.

5. The vanadium battery as described in claim 1, characterized in that, The preparation method of the imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane includes the following steps: (1) 100 parts of perfluorosulfonic acid resin were dissolved in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; (2) Mix the resin solution containing 100 parts of perfluorosulfonic acid resin and 5-10 parts of imidazole-grafted nano silica in a mixer in proportion, and obtain the film-forming liquid after degassing. (3) The film-forming solution is cast to obtain an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane.

6. The vanadium battery as described in claim 5, characterized in that, The specific steps of the casting film formation method are as follows: the film-forming liquid is added to the storage tank of the casting machine, the storage tank is kept at 105-110℃, and the film is cast on the transmission steel belt at 120-140℃ through the casting blade, with a film thickness of 0.05mm; the film is removed from the steel belt, and after fixing each side of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain an imidazole-grafted nano-silica modified perfluorosulfonic acid proton exchange membrane; the heating and shaping temperature is 160-170℃ and the time is 0.5-1h.

Citation Information

Patent Citations

  • Proton exchange membrane for medium-high temperature fuel cell and preparation method thereof

    CN101604757A

  • Ionic liquid covalently-bonded immobilized silicon-based material, and preparation method and application thereof

    CN111359585A